Church and state in Finland in 1999 - Seppo, Juha (European journal for church and state research, 2000)
Abstract der Zeitschrift: Since the late 1960's and the early 1970's there has been no intensive debate in Finland on religious and church policy. The demands of that time of radicalism to change the foundations of the Freedom of Religion Act and to implement radical changes in the relations between the State and Churches did not receive sufficient political support. Only minor adjustments were made to the Freedom of Religion Act, mainly concerning the procedure of secession from the Church. Demands for massive changes to the Freedom of Religion Act and for "the separation of Church and State" at the parliamentary level remained as occasional bills, which later miscarried